2005
DOI: 10.1088/0034-4885/68/5/r03
|View full text |Cite
|
Sign up to set email alerts
|

Sum-frequency generation spectroscopy of interfaces

Abstract: This paper reviews aspects of nonlinear optical spectroscopy of interfaces. The emphasis is put on second-order nonlinear optical techniques, such as sum-frequency generation (SFG), which possess intrinsic surface or interface selectivity and can therefore be used to probe buried interfaces accessible by light. The basic concepts of the second-order nonlinear response of surfaces and interfaces are given. While SFG in the ultraviolet-visible range allows one to achieve surface-specific electronic spectroscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
217
0
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(223 citation statements)
references
References 317 publications
(349 reference statements)
0
217
0
4
Order By: Relevance
“…Among the various vibrational spectroscopies, Raman and surface-enhanced Raman spectroscopy (SERS) are particularly useful for in situ studies of photoelectrode surfaces with high lateral spatial resolution, and thus form the focus of this section. Other vibrational spectroscopic techniques such as infrared reflection-absorption spectroscopy (IRAS) [127][128][129] and SFG [130][131][132] are also of great interest due to their ability to probe the molecular structure of solvent and adsorbate molecules at electrode surfaces, but can be limited by low sensitivity, energy restrictions that largely exclude the detection of lower frequency modes characteristic to metal-adsorbate complexes, and surface selection rules that exclude detection of adsorbate intramolecular vibrations that are oriented parallel to the interface. Raman spectroscopy is based on the inelastic scattering of light by a molecule or a solid, with the energy shifts of the scattered photons corresponding to quantized transitions in vibrational levels (molecule) or optical phonons (solids).…”
Section: Optical Spectroscopy Techniquesmentioning
confidence: 99%
“…Among the various vibrational spectroscopies, Raman and surface-enhanced Raman spectroscopy (SERS) are particularly useful for in situ studies of photoelectrode surfaces with high lateral spatial resolution, and thus form the focus of this section. Other vibrational spectroscopic techniques such as infrared reflection-absorption spectroscopy (IRAS) [127][128][129] and SFG [130][131][132] are also of great interest due to their ability to probe the molecular structure of solvent and adsorbate molecules at electrode surfaces, but can be limited by low sensitivity, energy restrictions that largely exclude the detection of lower frequency modes characteristic to metal-adsorbate complexes, and surface selection rules that exclude detection of adsorbate intramolecular vibrations that are oriented parallel to the interface. Raman spectroscopy is based on the inelastic scattering of light by a molecule or a solid, with the energy shifts of the scattered photons corresponding to quantized transitions in vibrational levels (molecule) or optical phonons (solids).…”
Section: Optical Spectroscopy Techniquesmentioning
confidence: 99%
“…8 The first molecular structure of water at the air/water interface using the surface-specific vibrational sum-frequency generation (SFG) technique was reported by Du et al 9 in 1993. 1,10 In that work, using the ''titration'' of dangling OH groups with methanol and hence the complete suppression of the peak of the free OH SFG signal, it was found that about 25% of surface water molecules have one dangling OH bond that is not H-bonded to other water molecules. It is thereby free, and protrudes out of the water phase, confirming earlier predictions from computations.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial overlap and temporal synchronisation of both incident laser pulses -the duration of which lays in the picosecond or femtosecond spectral ranges-induces the generation of SFG photons (Humbert et al, 2008;Y.R. Shen, 1989;Vidal & Tadjeddine, 2005;Williams & Beattie, 2002), which frequency is the sum of the frequencies of both initial ones (Howell et al, 2008;Ye et al, 2009). The SFG signal is enhanced while the IR beam excites a vibrational mode of the molecules adsorbed on the sample surface.…”
Section: Introductionmentioning
confidence: 99%